Bifurcations and a chaos strip in states of long Josephson junctions: Электpонные свойства металлов и сплавов - Yugay, K. N.; Blinov, N. V.; Shirokov, I. V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
Stationary and nonstationary, in particular, chaotic states in long Josephson junctions are investigated. Bifurcation lines on the parametric bias current-external magnetic field plane are calculated. The chaos strip along the bifurcation line is observed. It is shown that transitions between stationary states are the transitions from metastable to stable states and that the thermodynamical Gibbs potential of these stable states may be larger than for some metastable states. The definition of a dynamical critical magnetic field characterizing the stability of the stationary states is given.